A note on Placenticeras warthi Kossmat, 1895 (Ammonoidea), the type species of the genus Hypengonoceras Spath, 1922. (March 2020) - Roy, Arindam; Bardhan, Subhendu
Abstract: The type species Placenticeras warthi Kossmat, 1895 described from the Early Cretaceous (Albian) of South India is crucial for understanding the true affinity of the genus Hypengonoceras Spath, 1922. The species description was based on a holotype and was influenced by the erroneous and misleading hand sketches of the species published in the literature. We recently inspected the type specimen archived in Geological Survey of India, Kolkata, along with one additional specimen kept in Indian Museum, Kolkata, and redescribe them in the present study.